1508 Spectrum of Neural Tube Defects after Prenatal Antiepileptic Drug Exposure: Extensive Case Series. (October 2012) - Dijk, MH van; Bulk, S; Oppen, ACC van; Egberts, ACG; Heerdink, ER; Lindhout, D
Abstract : Background: Most pregnant women with chronic active epilepsy need to use antiepileptic drugs (AEDs) during pregnancy to prevent epileptic seizures that may threaten maternal and fetal well-being. Valproic acid (VPA) and carbamazepine (CBZ) have been associated with an increased risk of neural tube defects (NTDs) in the exposed fetus. Aim: To investigate the spectrum of neural tube defects and associated central nervous system (CNS) and non-CNS malformations after prenatal exposure to CBZ and/or VPA. Methods: NTDs in pregnancies in which CBZ and/or VPA were used during the first trimester were collected from 1970–2012 in the Netherlands. Type and location of the NTDs, associated CNS and non-CNS major malformations and relevant patient characteristics were analysed. Results: 87 pregnancies were included. NTDs after exposure to CBZ or VPA were mostly caudally located, whereas a combination of CBZ and VPA was associated with a location shift of the NTD to the rostral side (Figure 1 ). There were no differences between CBZ and VPA in the percentage of associated CNS malformations and non-CNS malformations circa 75% and 45%. Conclusions: The combination of VPA and CBZ shows a tendency towards a more rostral location (lumbar) which may have more severe functional consequences. Current findings confirm that NTDs associated fetal exposure to VPA and/or CBZ are serious and frequently accompanied by other CNS and non-CNS malformations. Funding: Netherlands Epilepsy Foundation (NEF) grant nr 03.18, University Medical Center Utrecht [NL] - institutional Genvlag grant.